Comparison of physical and chemical properties of ambient aerosols during the 2009 haze and non-haze periods in Southeast Asia - Xu, Jingsha; Tai, Xuhong; Betha, Raghu; He, Jun; Balasubramanian, Rajasekhar (Springer Netherlands, 2015)
Recurrent smoke-haze episodes that occur in Southeast Asia (SEA) are of much concern because of their environmental and health impacts. These haze episodes are mainly caused by uncontrolled biomass and peat burning in Indonesia. Airborne particulate matter (PM) samples were collected in the southwest coast of Singapore from 16 August to 9 November in 2009 to assess the impact of smoke-haze episodes on the air quality due to the long-range transport of biomass and peat burning emissions. The physical and chemical characteristics of PM were investigated during pre-haze, smoke-haze, and post-haze periods. Days with PM2.5 mass concentrations of ≥35 μg m−3 were considered as smoke-haze events. Using this criterion, out of the total 82 sampling days, nine smoke-haze events were identified. The origin of air masses during smoke-haze episodes was studied on the basis of HYSPLIT backward air trajectory analysis for 4 days. In terms of the physical properties of PM, higher particle surface area concentrations and particle gravimetric mass concentrations were observed during the smoke-haze period, but there was no consistent pattern for particle number concentrations during the haze period as compared to the non-haze period except that there was a significant increase at about 08:00, which could be attributed to the entrainment of PM from aloft after the breakdown of the nocturnal inversion layer. As for the chemical characteristics of PM, among the six key inorganic water-soluble ions (Cl−, NO3 −, nss-SO4 2−, Na+, NH4 +, and nss-K+) measured in this study, NO3 −, nss-SO4 2−, and NH4 + showed a significant increase in their concentrations during the smoke-haze period together with nss-K+. These observations suggest that the increased atmospheric loading of PM with higher surface area and increased concentrations of optically active secondary inorganic aerosols [(NH4)2SO4 or NH4HSO4 and NH4NO3] resulted in the atmospheric visibility reduction in SEA due to the advection of biomass and peat burning emissions.